Sosialisasi lubang Biopori di SMPN 270 Jakarta Utara - Safitri, Dini (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2019)
Students of State University of Jakarta (UNJ) D-III Study Program Public Relations conducted a socialization about the benefits of biopori holes through Community Service Activities (PKM). This activity was held at SMPN 270 Jakarta Utara. The objectives of this PKM activity are (1) Producing schools that are aware of the environment, (2) Informing about the functioning of Biopore Holes for the school environment, (3) Giving birth to organizations engaged in environmental preservation in schools, (4) Realizing a caring attitude towards the environment in school.